Under water ; Under earth - e uthor,e; e uthor,e (Somerville, Massachusetts : BPP, 2016)
Learn hundreds of fascinating facts as you dive below the surface, and find out what happens under the earth and under the water. From early submarines and deep-sea life, to burrowing animals and man-made tunnels - you will never look at the world in the same way again.
Under water -- Under earth.
5.5
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Oversize books -- Specimens; Underground areas; Underwater exploration; Oversize books; Underwater exploration; Earth; Upside-down books